Exploration and application of 3D CO2 storage leakage monitoring technology: A case study of Zhangjiaduo oilfield in Subei Basin - CHEN Xingming, QIAN Yanghui, CHEN Zhongzhi, CHEN Zifan (Youqicang pingjia yu kaifa)
As a critical component of Carbon Capture, Utilization, and Storage (CCUS) technologies, CO₂-enhanced oil recovery (CO2-EOR) has been widely used both domestically and internationally. This technology not only improves oil recovery but also enables large-scale CO₂ sequestration. However, potential CO₂ leakage risks exist throughout the processes of CO2 injection, displacement, sequestration, and production. Existing monitoring practices in domestic and international projects primarily focus on reservoirs and caprocks, with limited attention paid to systematic ecological environmental monitoring. CO₂-EOR development commenced in the Zhangjiaduo oilfield in 2014. As of now, a cumulative total of 195,300 tonnes of CO2 has been injected, resulting in an incremental oil production of 51,600 tonnes. The oil recovery rate was improved by 15.22%, and the phase oil replacement ratio reached 3.78, indicating remarkable stimulation effectiveness. Based on the Zhangjiaduo CO₂-EOR and sequestration project, a comprehensive 3D monitoring system was developed, integrating multiple indicators across groundwater, soil, and atmosphere to enable real-time monitoring and early warning of CO₂ leakage. After over one year of continuous monitoring, the results showed that the CO2 mass concentration in Zhangjiaduo groundwater remained stable at about 5,712 mg/m3, with a near-neutral pH and stable electrical conductivity ranging from 1.343 to 1.347 μS/cm. The CO2 mass concentration, pH, and conductivity in the soil also remained relatively stable. Atmospheric CO2 concentrations at three different altitudes exhibited periodic fluctuations consistent with soil data, averaging between 730 and 780 mg/m3, which aligns with typical atmospheric CO2 levels in low-latitude regions. These multi-parameter monitoring results indicate that no CO₂ leakage has occurred in the Zhangjiaduo oilfield to date. The successful application of this monitoring system has provided robust scientific support for the sustained development of the field. Moreover, it offers practical insights and references for environmental monitoring in similar projects, contributing to the safe and sustainable advancement of CO2-EOR technologies.